2019
DOI: 10.1029/2019gl084928
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Marine Heatwave Metrics to Ocean Model Resolution

Abstract: Sustained extreme temperature events in the ocean, referred to as marine heatwaves (MHWs), generate substantial ecological, social, and economic impacts. Ocean models provide insights to the drivers, persistence, and dissipation of MHWs. However, the sensitivity of MHW metrics to ocean model resolution is unknown. Here, we analyze global MHW metrics in three configurations of a global ocean-sea ice model at coarse (1 • ), eddy-permitting (0.25 • ), and eddy-rich (0.1 • ) resolutions. We show that all configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 36 publications
9
53
0
Order By: Relevance
“…The model's frontal structure and filaments of the ACC, climatological winter mixed layer, and vertical velocities have been shown to be in good agreement with observations (Langlais et al, 2017). OFAM's horizontal resolution (i.e., 1/10 • ) resolves mesoscale processes in highly energetic regions, and is therefore suitable for regional MHW studies (Pilo et al, 2019).…”
Section: Hindcast Ocean Model Outputsupporting
confidence: 59%
See 2 more Smart Citations
“…The model's frontal structure and filaments of the ACC, climatological winter mixed layer, and vertical velocities have been shown to be in good agreement with observations (Langlais et al, 2017). OFAM's horizontal resolution (i.e., 1/10 • ) resolves mesoscale processes in highly energetic regions, and is therefore suitable for regional MHW studies (Pilo et al, 2019).…”
Section: Hindcast Ocean Model Outputsupporting
confidence: 59%
“…Globally, modeled MHWs have been described to be less frequent, longer-lasting, and weaker than observed MHWs (Pilo et al, 2019). To the north of the KP, in contrast to the results in Pilo et al (2019), modeled MHWs are more intense than observed MHWs. To the west of the KP and on the plateau itself, however, results corroborate with those from the global analysis.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Western boundary currents are regions of fast and variable currents, where a substantial fraction of MHWs are generated by internal variability arising from local forcing and mesoscale processes, rather than large-scale climate modes 28 . Higher spatial resolution models outperform their lower resolution counterpart in simulating MHWs of recent decades 14 because they simulate realistic mean flow and mesoscale variability 13 . Our study demonstrates that coarse-resolution global climate models simulate less intense MHWs in western boundary current regions due to the lack of strong internal variability.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, western boundary currents are regions of intense eddy activity where high-resolution models simulate the historical mean state and variability better than the coarse-resolution models 13 . This includes the simulation of MHWs 14 . Therefore, the projected changes in MHWs in western boundary current regions may be better represented in higher-resolution models.…”
mentioning
confidence: 99%